Intellektuális akadálymentesítés az oktatásban: problémafelvetés, alternatívák keresése - KRASZNAY, Mónika (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2022)
Intellectual Accessibility in Education: Raising the Issue, Searching for Alternatives. Based on the author’s educational and teaching experiences, including a recommended literature, and taking into account the relevant context of the postmodern society (rapidly changing world, rapidly developing sciences, increased amount of but easily/quickly accessible information, communication tools for information dis-semination, etc.), the study considers – and encourages the reader to do the same – the following in terms of both secondary and higher education: ● How and to what extent can we supplement the one-sided memorization of facts and data, the acquisition of lexical knowledge with the technical possibilities of researching and storing information? ● What kind of intellectual abilities and skills, how much independent knowledge is needed today, the development of which should be given greater emphasis? ● How to relieve the burden of a student whose biggest problem is memorization and is this type of relief justified? ● How can the current aspects of accountability and evaluation be supplemented and/or changed accordingly? She does all of this inspired by the thoughts of some experts in the field, whose works form the basis of this study in addition to the author’s teaching and educational experiences. Although the approach to the topic is basically theoretical, the author tries to shape her professional work according to the outlined perspectives, to which concrete reference is made in the concluding part. The main goal of the study is to encourage further thinking, exchange of opinions, and professional discussions, in addition to raising the issue, going around the topic and drawing attention.